STRATEGI NGO BOS (BORNEO ORANGUTAN SURVIVAL) FOUNDATION DALAM MENYELAMATKAN ORANGUTAN DI KALIMANTAN TENGAH (2016-2019) - Qomariah, Anggi Nurul (Journal of Islamic World and Politics, 2020)
This paper will describe the BOS (Borneo Orangutan Survival) Foundation's strategy as an NGO in saving Orangutans. Orangutan is one of the endemic animals of the island of Borneo, which currently lives in threatened conditions.  Bornean Orangutans are in the endangered category and there are 57,000 individuals left. Even in the last 20 years the population of Bornean Orangutans has decreased by 55% due to illegal logging, clearing of oil palm land and poaching. It was also agreed through the Convention on International Trade in wild plants and animals or the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) that Orangutans are one of the endangered primates and are animals that we must protect. To face this situation, the BOSF is implementing a strategy or way through social media campaigns with the #ClimbForOrangutan, #OrangutanFreedom and #SaveDodo strategies. Another strategy undertaken by the BOS Foundation to continue to fight in saving orangutans and their habitats is to work with overseas partners and organizations that also focus on animal rescue and conservation.Keywords: BOS, Orangutan, NGO